Effects of Antisense Oligonucleotides against C-Reactive Protein on the Development of Atherosclerosis in WHHL Rabbits - Qi Yu; Zhengcao Liu; Ahmed Bilal Waqar; Bo Ning; Xianghong Yang; Masashi Shiomi; Mark J. Graham; Rosanne M. Crooke; Enqi Liu; Sijun Dong; Jianglin Fan (Mediators of Inflammation)
Increased plasma levels of C-reactive protein (CRP) are closely associated with cardiovascular diseases, but whether CRP is directly involved in the pathogenesis of atherosclerosis is still under debate. Many controversial and contradictory results using transgenic mice and rabbits have been published but it is also unclear whether CRP lowering can be used for the treatment of atherosclerosis. In the current study, we examined the effects of the rabbit CRP antisense oligonucleotides (ASO) on the development of atherosclerosis in WHHL rabbits. CRP ASO treatment led to a significant reduction of plasma CRP levels; however, both aortic and coronary atherosclerotic lesions were not significantly changed compared to those of control WHHL rabbits. These results suggest that inhibition of plasma CRP does not affect the development of atherosclerosis in WHHL rabbits.